Survival of patients with pancreatic ductal adenocarcinoma - Targarona, Javier (2023)
Objective: The objective of this study is to analyze the epidemiological presentation and survival of patients with pancreatic ductal adenocarcinoma according to their clinical stage and the type of intervention performed, in a cohort of patients treated at a clinic in Lima, Peru. Materials and methods: A retrospective cohort study evaluated patients diagnosed with pancreatic ductal adenocarcinoma from January 2015 to February 2021, considering various epidemiological factors, radiological findings, oncological staging, receipt ofneoadjuvant or adjuvant chemotherapy, undergoing surgery, and post-intervention survival. Results: Out of the 249 patients analyzed, 75 of them required resective surgery. Among the main findings, it was observed that those with a CA 19-9 level below 200 U/mL had a higher median survival compared to those with a CA 19-9 level above 200 U/mL (HR: 1.96; 95% CI: 0.18-0.53; p≤0.001). Furthermore, when comparing patients according to their stage, those with resectable tumors had a median survival of 37.72 months, while those with locally advanced tumors had a median survival of 13.47 months, and those with metastatic tumors had a median survival of 7.69 months (HR: 0.87; 95% CI: 0.31-0.25; p≤0.001). Additionally, receiving neoadjuvant treatment was associated with a better prognosis of survival for patients (HR: 0.32; 95% CI: 0.19-0.53; p≤0.001). Furthermore, 5 pancreatectomies with metastatic resection were performed in oligometastatic patients treated with salvage chemotherapy, and the median survival for these patients was 22.51 months. Conclusion: Resective surgery at an early clinical stage, CA 19-9 levels below 200 U/mL, and receiving neoadjuvant chemotherapy are statistically correlated with a higher overall survival.